Cholesterol uptake capacity: A new measure of high-density lipoprotein functionality as a predictor of subsequent revascularization in patients undergoing percutaneous coronary intervention. (March 2022) - Fujimoto, Daichi; Otake, Hiromasa; Kawamori, Hiroyuki; Toba, Takayoshi; Nagao, Manabu; Nakano, Shinsuke; Tanimura, Kosuke; Takahashi, Yu; Fukuyama, Yusuke; Kakizaki, Shunsuke; Nakamura, Koichi; Harada, Amane; et al.
Abstract: Background and aims: High-density lipoprotein (HDL) functionality is an important determinant of coronary artery disease (CAD) development. We recently developed cholesterol-uptake capacity (CUC), a rapid cell-free assay system that directly evaluates the capacity of HDL to accept additional cholesterol. We aimed to evaluate the association between CUC and revascularization in patients who have undergone percutaneous coronary intervention (PCI). Methods: We retrospectively reviewed patients who underwent PCI with subsequent revascularization or coronary angiography (CAG) without revascularization. The patients who had frozen blood samples for which CUC were measurable at the index PCI and follow-up were enrolled. Results: We finally enrolled 74 patients who underwent subsequent revascularization and 183 patients who underwent follow-up CAG without revascularization. The serum CUC level at the index PCI was significantly lower in the revascularization group than that in the non-revascularization group (84.3 [75.2–98.9] vs. 92.0 [81.6–103.3 A U.]; p = 0.004). Multivariate logistic regression analysis revealed that decreased serum CUC level at the index PCI was independently associated with subsequent revascularization (odds ratio, 0.98; 95% confidence interval, 0.969–1.000). After adjusting for 16 cardiovascular risk factors, the serum CUC level at the index PCI and follow-up and the absolute change in serum CUC level from the index PCI to follow-up were significantly lower in the revascularization group than those in the non-revascularization group. Conclusions: Serum CUC level at index PCI was independently associated with subsequent revascularization after PCI. Continuous assessment of HDL functionality by CUC might help predict subsequent revascularization after PCI. Graphical abstract: Image 1 Highlights: Cholesterol-uptake capacity (CUC) is a simple and rapid cell-free assay to evaluate high-density lipoprotein (HDL) functionality. CUC directly evaluates the capacity of HDL to accept additional cholesterol. Lower serum CUC at index percutaneous coronary intervention (PCI) was associated with subsequent revascularization. Decreased change value in CUC during the follow-up in the revascularization group.